Pengalaman dan Strategi Pelaku Usaha Kecil Dalam menghadapi Tantangan Bisnis Unutuk Penerapan Mahasiswa Wirausaha - Fani Fani; Almunawwara; Lidya olivia balanda; Fikra Fikra; Dyo moh Sabda; Nuraisyah Nuraisyah; Andi Maman Firmansyah; Fachrul Reza (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This study examines the experiences and strategies of small business owners (MSMEs) in dealing with business challenges such as limited capital, fierce competition, and rising raw material prices, as a learning tool for entrepreneurial students. The background is based on the high failure rate of MSMEs due to a lack of adaptation, thus requiring practical studies to equip students with real skills. The purpose of this study is to identify effective MSME strategies to improve the business resilience of students. The method used is qualitative, with in-depth interviews and observations of MSME actors on Jln. Biologis, Tondo Village, Mantikulore District, Palu City. The results indicate that the main strategies include being able to compete in marketing, product innovation, and maintaining the business, as well as viewing challenges as opportunities for business growth and development. The results of this study can be used as a basis for better development policies in supporting the growth and sustainability of SMEs.